An experimental model of chronic osteomyelitis induced by staphylococcus aureus in New Zealand white rabbit - Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Aziz, Aziah; Ibrahim, Mohd Zulfadzli (2017)
The New Zealand White Rabbit (NZWR) is an established model for osteomyelitis. The objective of this study was to induce chronic osteomyelitis in New Zealand White Rabbit distal femoral shaft. This study is a descriptive analysis of the surgical approach (and related complications) used for development of osteomyelitis at distal femur in the NZWR model. This study was performed at Advanced Orthopaedic Research Laboratory, International Islamic University Malaysia that followed the requirements of ISO/IEC17025:2005 standard. Surgical introduction of the staphylococcus aureus was done via a drilled hole at lateral part of distal femur of NZWR. Fifty centiliters of distilled water was used to clear the intramedullary of femur. Staphylococcus aureus (ATCC 25923) with 2x106 cfu was introduced via the drilled hole of the lateral distal femur of the NZWR. The muscles were closed by layers. Assessment of the pre inoculation after 3 weeks post inoculation was done. The radiology, weight and bacteriology analysis was done. After 3 weeks post inoculation, radiological findings showed significant changes on the affected area (p<0.05). Weight reduction was significant in the post inoculation (p<0.05). The bacteriology assessments consisted of nutrient agar culture; coagulase and catalase tests confirmed that staphylococcus aureus was isolated from all the subjects. No mortality was recorded among all rabbits involved in this study. This study revealed a positive achievement in the development of osteomyelitis model through this protocol. We recommend this simple and reliable surgical procedure via femoral shaft for the creation of osteomyelitis model in NZWR